The Daap Sung Man - Low, Xin Yi (SARE: Southeast Asian Review of English, 2023)
This essay is centered around my experiences with the daap sung man during my childhood: a food delivery service I depended on for routine and familiarity. My piece reflects on the loss of continuity and the overwhelming freedom of choice that came with the disappearance of the service that followed soon after as technology started developing and the service was eventually discontinued. The absence of the daap sung man followed my dependence on self-destructive habits for the familiarity of being a "prisoner" to routine. It also muses on the passing of time and how the daap sung man’s era has now become a distant story of the past, but the comfort it once provided in a time where abuse was prevalent in my family would forever permeate my memories. *daap sung (or 搭餸), refers to door-to-door catering services, most commonly brought in tiffin carriers (gaa laam or 格篮 in Cantonese) as illustrated in this article. Please note that it is not a commonly used term in the Malaysian Chinese community but rather a unique term coined by my (the author’s) parents.